An Abscess Causing a Delayed Optic Neuropathy after Decompression for Thyroid Eye Disease. (February 2014) - Patel, Rakesh M.; Aakalu, Vinay K.; Joe, Stephanie; Setabutr, Pete
ABSTRACT A 63-year-old female with Graves' disease and chronic sinusitis presented with acute left orbital pain and proptosis five years after bilateral orbital decompression and sinus surgery. Imaging revealed bilateral frontal sinus opacification, frontoethmoidal mucoceles and left subperiosteal mass. Presence of an optic neuropathy drove emergent management with intravenous antibiotics and orbitotomy with exploration. Intra-operatively, a left orbital abscess and left frontal sinus purulence were drained. The patient regained her vision with relief of proptosis and pain.